COMMUNICATIVE COMPETENCE OF ENGLISH TEACHERS - Kareva, Veronika (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
Learners’ accomplishments depend to a great extent on the knowledge and skills of their teachers. In order to be able to develop students’ potential, teachers need to have competences for a high quality education and opportunities for professional growth. English communicative competence is an important aspect of teacher expertise. The aim of this paper is to show how novice teachers evaluate their own communicative competence, the ways they developed it during their studies and the possibilities for improvement after graduation. 26 novice teachers graduated from the South East European University (SEEU), participated in the study. The results gathered from their reports are expected to identify the areas for improvement in teacher education curricula at this particular university and generally, in the countries where English is taught as a foreign language and by non-native speakers.